The structure and dynamics of nano particles encapsulated by the SDS monolayer collapse at the water/TCE interface - Shi, Wenxiong (2018)
The super-saturated surfactant monolayer collapses with the nanoparticles (NPs) at the water/trichloroethylene (TCE) interface are investigated using molecular dynamics (MD) simulations. The results show that sodium alkyl sulfate (SDS) monolayer collapse is initiated by buckling and followed primarily by budding and the bud encapsulating the NPs and oil molecules. The developed bud detaches from the monolayer into a water phase and forms the swollen micelle emulsion with NPs and oil molecules. We investigate the wavelength of the initial budding and the theoretical description of the budding process. The wavelength of the monolayer increases with bending modulus. The energy barrier of the budding can be easily overcome by thermal fluctuation energy, which indicates that budding process proceeds rapidly.